EFEKTIVITAS PEMBELAJARAN BERBASIS PROYEK DALAM MENGEMBANGKAN KETERAMPILAN ABAD 21 - Maftuhatul Jannah; Rahma Aqila Putri; Viana Zaharani; Tatu Hilaliyah (Program Studi Pendidikan Bahasa dan Sastra Indonesia, FKIP, Universitas Halu Oleo Kampus Bumi Tridharma Andounohu Kendari, Provinsi Sulawesi Tenggara – Indonesia, 2025)
The purpose of this research is to analyze the effectiveness of project-based learning (PJBL) for students of SMPN 14 Serang City. This method centers on the critical thinking process and communication between students. The challenge faced by students in this learning is how they can solve the problems that occur and how to communicate well in the group.